PENERAPAN METODE BACKWARD CHAINING PADA SISTEM PAKAR UNTUK MENDETEKSI PENYAKIT TANAMAN JAGUNG - Hamsinar, Henny; Musadat, Fithriah; Rahayu, Rahayu (Prodi Teknik Informatika Unidayan Baubau, 2019)
Corn plant disease is one of the obstacles to success in cultivating corn in Ngkari-ngkari Village. Farmers do not yet fully know how to deal with the symptoms of corn plant disease. This study aims to create an expert system application to detect maize plant diseases, to determine the type of disease and the solution used is the backward chaining method approach starting from the Goal then looking for facts that match the premise data. This research resulted in an application that can help users to detect symptoms of corn plant diseases and provide prevention or control solutions if there are corn farmers that are detected by disease symptoms.Keyword: Backward Chaining, Expert system, Corn plant